Carrera de Comunicación de la Facultad de Ciencias Administrativas logró triunfar en el concurso La Voz de Oro 2023 - García García, Mariana (2023)
UNIT OF COMMUNICATION PRESS RELEASE 062 Guaranda, June 26, 2023 Communication Major of the Faculty of Administrative Sciences managed to succeed in the 2023 Golden Voice contest The State University of Bolívar and the Faculty of Administrative Sciences proud of fellow students of the Communication major, who participated in the “The Golden Voice 2023” contest, an activity organized by the Technical University of Ambato (UTA), the speech capabilities were evaluated, considering its uniform sound, intonation, voice level among others, managing to place themselves on the podium of this contest as follows: First Place: Washington Valverde. (6th cycle) Second Place: William Vega. (8th cycle) Third Place: Silvia Gualán Guayas (8th cycle